Hypoxic pulmonary hypertension in mice with constitutively active platelet-derived growth factor receptor-β - Dahal, Bhola K. (Medknow Publications, 2011)
Platelet-derived growth factor (PDGF) has been implicated in the pathobiology of vascular remodeling. The multikinase inhibitor imatinib that targets PDGF receptor (PDGFR), c-kit and Abl kinases, shows therapeutic efficacy against experimental pulmonary hypertension (PH); however, the role of PDGFR-b in experimental PH has not been examined by genetic approach. We investigated the chronic hypoxia-induced PH in mice carrying an activating point mutation of PDGFR-β (D849N) and evaluated the therapeutic efficacy of imatinib. In addition, we studied pulmonary global gene expression and confirmed the expression of identified genes by immunohistochemistry. Chronically hypoxic D849N mice developed PH and strong pulmonary vascular remodeling that was improved by imatinib (100 mg/kg/day) as evident from the significantly reduced right ventricular systolic pressure, right ventricular hypertrophy and muscularization of peripheral pulmonary arteries. Global gene expression analysis revealed that stromal cell derived factor SDF)-1α was significantly upregulated, which was confirmed by immunohistochemistry. Moreover, an enhanced immunoreactivity for SDF-1α, PDGFR-β and CXCR4, the receptor for SDF-1α was localized to the α-smooth muscle cell (SMC) actin positive pulmonary vascular cells in hypoxic mice and patients with idiopathic pulmonary arterial hypertension (IPAH). In conclusion, our findings substantiate the major role of PDGFR activation in pulmonary vascular remodeling by a genetic approach. Immunohistochemistry findings suggest a role for SDF-1α/CXCR4 axis in pulmonary vascular remodeling and point to a potential interaction between the chemokine SDF-1 and the growth factor PDGF signaling. Future studies designed to elucidate an interaction between the chemokine SDF-1 and the PDGF system may uncover novel therapeutic targets.